Math, asked by khushi15686, 2 months ago


lim \: x \:  \to \: 2 \:  \frac{x +  {x}^{2} +  {x}^{3}   - 14}{ {x}^{2} - 4 }

Please don't use method of differentiation.

Don't spam please.​

Answers

Answered by mathdude500
5

\large\underline{\sf{Solution-}}

Given expression is

\rm :\longmapsto\:\displaystyle\lim_{x \to 2} \:  \frac{x +  {x}^{2}  +  {x}^{3}  - 14}{ {x}^{2}  - 4}

If we substitute directly x = 2, we get

\rm \:  =  \: \dfrac{2 +  {2}^{2}  +  {2}^{3}  - 14}{ {2}^{2}  - 4}

\rm \:  =  \:\dfrac{2 + 4 + 8 - 14}{4 - 4}

\rm \:  =  \:\dfrac{14 - 14}{4 - 4}

\rm \:  =  \:\dfrac{0}{0}

which is indeterminant form.

Consider, again

\rm :\longmapsto\:\displaystyle\lim_{x \to 2} \:  \frac{x +  {x}^{2}  +  {x}^{3}  - 14}{ {x}^{2}  - 4}

can be rewritten as

\rm \:  =  \:\:\displaystyle\lim_{x \to 2} \:  \frac{x +  {x}^{2}  +  {x}^{3}  - (2 + 4 + 8)}{ {x}^{2}  - 4}

\rm \:  =  \:\:\displaystyle\lim_{x \to 2} \:  \frac{x +  {x}^{2}  +  {x}^{3}  - 2  -  4  -  8}{ {x}^{2}  - 4}

\rm \:  =  \:\:\displaystyle\lim_{x \to 2} \:  \frac{(x - 2)+({x}^{2} - 4) + ({x}^{3} - 8)  }{ {x}^{2}  - 4}

\rm \:  =  \:\:\displaystyle\lim_{x \to 2} \:  \frac{(x - 2)+({x}^{2} -  {2}^{2} ) + ({x}^{3} -  {2}^{3} )  }{ {x}^{2}  -  {2}^{2} }

We know,

\boxed{ \tt{ \:  {x}^{2} -  {y}^{2} = (x + y) (x - y) \: }}

and

\boxed{ \tt{ \:  {x}^{3} -  {y}^{3} = (x  -  y) ( {x}^{2} +  {y}^{2}  + xy) \: }}

So, using these, we get

\rm \:  =  \:\displaystyle\lim_{x \to 2} \frac{(x - 2) + (x - 2)(x + 2) + (x - 2)( {x}^{2} + 2x +  {2}^{2} )}{(x - 2)(x + 2)}

On cancelation the factor x - 2 from numerator and denominator, we get

\rm \:  =  \:\displaystyle\lim_{x \to 2} \frac{1 + (x + 2) + ( {x}^{2} + 2x + 4)}{(x + 2)}

\rm \:  =  \:\dfrac{1 + (2 + 2) + (4 + 4 + 4)}{2 + 2}

\rm \:  =  \:\dfrac{17}{4}

Hence,

\rm :\longmapsto\:\boxed{ \tt{ \: \displaystyle\lim_{x \to 2} \:  \frac{x +  {x}^{2}  +  {x}^{3}  - 14}{ {x}^{2}  - 4}  =  \frac{17}{4}}}

Additional Information :-

\boxed{ \tt{ \: \displaystyle\lim_{x \to 0} \frac{sinx}{x} = 1 \: }}

\boxed{ \tt{ \: \displaystyle\lim_{x \to 0} \frac{tanx}{x} = 1 \: }}

\boxed{ \tt{ \: \displaystyle\lim_{x \to 0} \frac{log(1 + x)}{x} = 1 \: }}

\boxed{ \tt{ \: \displaystyle\lim_{x \to 0} \frac{ {e}^{x}  - 1}{x} = 1 \: }}

\boxed{ \tt{ \: \displaystyle\lim_{x \to 0} \frac{ {a}^{x}  - 1}{x} = loga \: }}

Similar questions